Szlafrok i skarpetki, czyli intymność na scenie. O gdańskim spektaklu „Życie intymne Jarosława” (2020) w reżyserii Kuby Kowalskiego - Zwolińska, Barbara (Załącznik Kulturoznawczy, 2024)
In the article I look at the way of using literary sources by Jarosław Iwaszkiewicz (epistolary and diary entries) and Karol Szymanowski (fragments of the novel Efebos) in the performance of the Wybrzeże Theater in Gdańsk. The basis for the staging was the text Jarosław’s Intimate Life, co-authored by Magda Kupryjanowicz and Michał Kurkowski, published in 2020 in “Dialog”. A special source of inspiration for the creators of the script, apart from Efebos, were the diaries of both Anna and Jarosław Iwaszkiewicz, as well as the collection of letters from the author of Brzezina to Jerzy Błeszyński, Everything as you want, published in 2017, edited by Anna Król. I am interested in possible readings of the performance, ranging from the biographical context to the universal and contemporary one, related to manifestation of the right to love, freedom of choice and tolerance. The intimacy on stage and its setting in the form of scenography, light and sound, exposed by the play of actors cast in one or more roles, are part of the director’s vision, focused not only on the complicated relationship of two men (emphasized in the idea of multiplying the character of Jerzy), but in general on man, seeking an escape from loneliness and transience in eroticism. It is an intimacy that combines the sublime with the trivial, the sincerity of despair with theatricality and kitsch, revealing the paradox of death, which reverses the natural order of existence.